The Relationship of Primipara Mother's Knowledge and Mother's Attitudes in Preventing Wasting Incidents in the Clinic Pratama Bunda Anzef District Pancur Batu Deli Serdang - Elsa Nurcahya; Debi Novita Siregar; Butet Oxtaviana Purba; Dina Riani Saragih; Ellis Endang Purwasih; Diana Teresia (JURNAL KEBIDANAN KESTRA (JKK), 2025)
Wasting is a nutritional problem characterized by a mismatch between a child's weight and height or their z-score, resulting in significant weight loss or being far below the normal range. The aim of this study is to examine the relationship between the knowledge of primiparous mothers and their attitudes toward preventing wasting at the Bunda Anzef Primary Clinic, Pancur Batu District, Deli Serdang. This study is a quantitative observational research using a cross-sectional approach. The sample consisted of 52 respondents, selected through purposive sampling. Data analysis was conducted univariately and bivariately using the chi-square test. The results showed that the majority of respondents had insufficient knowledge about wasting, with 26 respondents (50%) having limited understanding. Furthermore, most respondents exhibited negative attitudes toward preventing wasting, with 31 respondents (59.6%) showing this tendency. A significant relationship was found between the knowledge of primiparous mothers and their attitudes toward preventing wasting, with a p-value of 0.001 (p<0.05). The conclusion of this study is that there is a relationship between the knowledge of primiparous mothers and their attitudes toward preventing wasting at the Bunda Anzef Primary Clinic, Pancur Batu District, Deli Serdang.